Ultrasound in the diagnosis of diaphragmatic paralysis after operation for congenital heart disease. Issue 1 (July 1990) - Balaji, S; Kunovsky, P; Sullivan, I
Abstract : Phrenic nerve palsy is a recognised complication of operation for congenital heart disease in children. The accuracy of ultrasound in assessing diaphragmatic motion was prospectively compared with fluoroscopy in 16 patients in whom phrenic nerve palsy was suspected. Ultrasound successfully identified the five patients with phrenic nerve palsy; there were no false positive or false negative diagnoses. Ultrasound was as effective as fluoroscopy in the diagnosis of abnormalities of diaphragmatic motion.